Behavior of a Glycerol Aqueous Droplet Impacting a Thin Water Film - J. Zhu; B. Liu; J. Sheng; S. Zheng; T. Lu; X. Chen (Journal of Applied Fluid Mechanics)
The dynamic behavior of a glycerol aqueous droplet impacting on a thin water film was experimentally investigated with a high-speed camera. Numerous splash behaviors with different impact velocities (2.0-4.5 m/s), liquid film thicknesses (140-700 μm) and glycerol solution concentrations (30 wt%, 60 wt% and 80 wt%) were statistically analyzed, and finally classified based on morphological features. The laser-induced fluorescence images illustrate that the prompt splash secondary droplets mainly originated from the thin water film, while the components of delayed splash secondary droplets came from both the glycerol aqueous droplet and the thin water film. The results show that increasing viscosity suppresses prompt splash,  inhibits the crown expansion and accelerates the crown collapse, while decreasing droplet viscosity facilitates prompt splash. The decreasing film thickness promotes passive delayed splash and increases the crown height. A splash morphology regime map was presented based on Weber number, dimensionless film thickness and solution mass concentration, delineating a threshold between prompt splash and coalescence. It also found that the occurrence of crown lamella rupture is sensitive to the film thickness and We.